2003
DOI: 10.1081/sac-120017504
|View full text |Cite
|
Sign up to set email alerts
|

Exact EDF Goodness-of-Fit Tests for Inverse Gaussian Distributions

Abstract: Exact EDF goodness-of-fit tests for inverse Gaussian ðm, Þ distributions in different cases of unknown parameters are constructed. In the case m is unknown and is known, a chi-square test is also proposed. The powers of the tests are estimated by Monte Carlo method at several different alternative distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The authors show that both procedures yield the same asymptotic null distribution. Exact edf tests for the IG2 were proposed by Nguyen and Dinh [12] but Gracia-Medrano and O'Reilly [13] showed that they have inferior power performance in small samples as compared with the tests of Edgeman et al [8] and O'Reilly and Rueda [11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors show that both procedures yield the same asymptotic null distribution. Exact edf tests for the IG2 were proposed by Nguyen and Dinh [12] but Gracia-Medrano and O'Reilly [13] showed that they have inferior power performance in small samples as compared with the tests of Edgeman et al [8] and O'Reilly and Rueda [11].…”
Section: Introductionmentioning
confidence: 99%
“…The methods by [8,9] are based on a characterization of the IG family by an independence property. In [10] a connection to the so-called random walk distribution is used, and [11] proposes exact tests based on the empirical distribution function of transformations characterizing the inverse Gaussian law, which are corrected in [12]. The author of [13] use a differential equation that characterizes the Laplace transform of the IG family as well as an L 2 -distance test, both using the empirical Laplace transform.…”
Section: Introductionmentioning
confidence: 99%
“…This testing problem has been considered in the statistical literature. The methods by Baringhaus and Gaigall (2015) and Mudholkar et al (2001) are based on a characterization of the IG family by an independence property, Ducharme (2001) uses a connection to the so called Random Walk distribution, and Nguyen and Dinh (2003) propose exact tests based on the empirical distribution function of transformations characterising the inverse Gaussian law, which are commented and corrected in Gracia-Medrano and O'Reilly (2005). Henze and Klar (2002) use a differential equation that characterizes the Laplace transform of the IG family as well as a L 2 -distance test, both using the empirical Laplace transform.…”
Section: Introductionmentioning
confidence: 99%